Evaluation of Science Teacher Education Programs. - Hermann, Graham D.; Willings, Rex (Science Education, 1980)
The article evaluates the education program for science teachers in the U.S. This study was undertaken to investigate the evaluation methodologies advocated in the American academic institutions. This is also to investigate the usefulness to understanding evaluation findings for the development of a newer methodologies involving ordering theory. The results indicate that congruency-discrepancy approaches were found to be useful in evaluating the intrinsic worth of curriculum objectives, especially if a rank-order analysis is used.